2008
DOI: 10.1038/jp.2008.55
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early and late umbilical cord clamping on neonatal hematocrit

Abstract: Objective: To compare the effect of early and late cord clamping (LCC) on neonatal hematocrit at 2 and 18 h of life.Study Design: In this double-blind randomized trial, 64 healthy fullterm vaginally born neonates were randomly allocated to either early (30 s) or late (3 min) umbilical cord clamping. During the interval between delivery and cord clamping, the attendant held the neonate supine at the level of the introitus. Neonatal venous hematocrit was measured at 2 and 18 h of life.Result: Neonatal hematocrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 14 publications
2
40
0
2
Order By: Relevance
“…18,19 Similar to prior work, we found delayed cord clamping is associated with a higher birth hematocrit and reduced need for red blood cell transfusions in the first week of life compared to neonates born prior to the initiation of the protocol. Furthermore, we identified that delayed cord clamping is associated with a decrease in the total number of red blood cell transfusions required over the course of a neonate’s hospitalization.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…18,19 Similar to prior work, we found delayed cord clamping is associated with a higher birth hematocrit and reduced need for red blood cell transfusions in the first week of life compared to neonates born prior to the initiation of the protocol. Furthermore, we identified that delayed cord clamping is associated with a decrease in the total number of red blood cell transfusions required over the course of a neonate’s hospitalization.…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, our data suggest benefits and lack of adverse outcomes associated with delayed cord clamping in a non-trial setting similar to those in a trial setting. 7,8,18,19 Furthermore, our study suggests delayed cord clamping was not associated with inability to collect cord blood gases, as cord blood gases were still recorded for more than 70% of delayed cord clamping patients.…”
Section: Discussionmentioning
confidence: 62%
“…The authors noted that placental blood is rapidly transferred into the neonate following birth and delays of 60 -180 s can have significant effects on the volumes of blood transferred to the baby at birth. Jahazi et al [13] note that when the umbilical cord is clamped immediately, as much as 30% of the neonate's blood can remain in the placenta. For the first 20 -25 seconds of life, blood continues to flow in the umbilical arteries from the newborn to the placenta.…”
Section: Effects On Hematocrit Hemoglobin and Blood Volumementioning
confidence: 99%
“…V literaturi opisane prednosti OPP pred TPP za donošene otroke so predvsem višja raven hemoglobina in feritina, večje zaloge železa in zmanjšana pojavnost anemije zaradi pomanjkanja že-leza, boljša kardiopulmonalna prilagoditev zaradi povečane perfuzije organov in daljše trajanje zgodnjega dojenja. 4,6,7,12,15,17,18 Omenjajo tudi boljše preživetje pri malariji v endemičnih regijah, zaradi kompetitivnega učinka med svincem in železom pa OPP zniža tudi raven svinca v obtoku v okoljih z onesnaženim zrakom.17 Prav tako predpostavljajo, da imajo zarodne celice v popkovnični krvi številne zaščitne in preventivne učinke v otrokovem razvijajočem se organizmu. Preprečevale naj bi pojav določenih krvnih in imunoloških bolezni.…”
Section: Prednosti Odložene Prekinitve Popkovnice Za Novorojenčkaunclassified